Optimalisasi Sistem Penagihan Air untuk Pelanggan Menunggak di PDAM Tirta Daroy Kota Banda Aceh - Rahmaniar, Rahmaniar (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
Many people already use PDAM Tirta Daroy water and many customers are often in arrears in payments due to the postpaid nature of the water payments. Some customers from PDAM Tirta Daroy had to have their water flow cut off because there were many unpaid arrears. Disconnection of meters or water flow is not carried out suddenly but through notification of arrears to customers. The purpose of this research is to determine the collection system for water account receivables that are in arrears at PDAM Tirta Daroy, Banda Aceh City. This research was carried out at the PDAM Tirta Daroy office, Teuku Nyak Arief Branch, Banda Aceh City. This research used qualitative methods and field research. The research results show that the procedures for collecting water account receivables at PDAM Tirta Daroy Teuku Nyak Arief Branch have been carried out in accordance with established work procedures, through the following stages (a) issuing a warning letter. (b) implementation of billing (c) issuance and implementation of termination letters and (d) cutting off water flow. Customers who are in arrears in paying their water bills for 3 (three) months and have received a warning letter, but have not yet made the payment, will experience their water flow being cut off by PDAM Tirta Daroy Banda Aceh technical officers